Juvenile xanthogranuloma. Report of 2 cases and review of literature. - Crespi, H.G.; Fligler, F.; Mijal, G.; Casas, J. (European Journal of Pediatric Dermatology, 1997)
Juvenile xanthogranuloma (JXG) is a benign, cutaneous, self-healing, infantile proliferation of non-X histiocytes. JXG is clinically characterized by yellowish papules and nodules. The Authors present two children with numerous skin lesions and review the relevant literature.